Macroscopic and microscopic electrochemical investigation of Clostridium botulinum C2IIa embedded in supported lipid membranes. (10th August 2016) - Frey, C.M.; Eifert, A.; Schütz, H.; Barth, H.; Mizaikoff, B.; Kranz, C.
Abstract: A hybrid membrane system based on 1-octadecanethiol (ODT) and 1-palmitoyl-2-oleoyl- sn -glycero-3-phosphocholine (POPC) has been investigated in respect to the incorporation of the transport component C2IIa of Clostridium botulinum C2 toxin into such bilayers. Such model systems are particularly interesting surrogates for studying fundamental transport phenomena across cell membranes. Here, we present structural and electrochemical studies at a model ODT-POPC hybrid membrane system established at a solid gold support substrate before and after the incorporation of pores. Pore incorporation was investigated via macroscopic electrochemical characterization using cyclic voltammetry (CV), and microscopic studies using atomic force microscopy (AFM) and AFM-scanning electrochemical microscopy (SECM) recording current-distance curves at the supported lipid membranes (SLMs) before and after the incorporation of pores. Recently developed AFM-SECM probes with integrated conical platinum composite electrodes were used for these spatially resolved studies. Finally, control experiments blocking the pores were performed using chloroquine (CQ), which is a known inhibitor for C2IIa proteins. The number of C2IIa pores incorporated in an ODT-POPC hybrid membrane was determined as 6.6*10 4 pores/mm 2 based on the single pore conductance model. Blocking with chloroquine has significantly reduced the number of active pores to 2.6*10 4 pores/mm 2 . To the best of our knowledge, the associated visualization via AFM was accomplished for the first time.